Nanomedicine for Diagnosis and Treatment of Cardiac Fibrosis - Montano-Peguero Y; Verdejo HE; Riquelme JA; Kogan MJ; Lavandero S (International Journal of Nanomedicine)
Yanay Montano-Peguero,1 Hugo E Verdejo,1,2 Jaime A Riquelme,1 Marcelo J Kogan,1,3 Sergio Lavandero1,4 1Advanced Center for Chronic Diseases (ACCDiS), Facultad de Ciencias Químicas y Farmacéuticas and Facultad Medicina, Universidad de Chile, Santiago, Chile; 2División de Enfermedades Cardiovasculares, Facultad de Medicina, Pontificia Universidad Católica de Chile, Santiago, Chile; 3Departamento de Química Farmacológica y Toxicológica, Facultad de Ciencias Químicas y Farmaceuticas, Universidad de Chile, Santiago, Chile; 4Cardiology Division, University of Texas Southwestern Medical Center, Dallas, TX, USACorrespondence: Marcelo J Kogan, Advanced Center for Chronic Diseases (ACCDiS), Facultad de Ciencias Químicas y Farmacéuticas, Universidad de Chile, Santiago, 8380494, Chile, Email mkogan@ciq.uchile.cl Sergio Lavandero, Advanced Center for Chronic Diseases (ACCDiS), Facultad de Ciencias Químicas y Farmacéuticas, Universidad de Chile, Santiago, 8380494, Chile, Email slavander@uchile.clAbstract: Cardiovascular diseases (CVDs) are the leading cause of death worldwide. Although different risk factors condition the evolution and outcome of CVDs, a limited number of common pathological pathways converge in adverse cardiac remodeling. Among these, cardiac fibrosis has been postulated not only as a mechanism for the onset and development of CVDs but also as a predictor of disease severity. Tools to diagnose subclinical cardiac fibrosis and therapies targeting cardiac fibrosis constitute an essential line of research in CVDs. To date, magnetic resonance imaging (MRI) is a sensitive tool for diagnosing cardiac fibrosis, but sampling errors can occur. Moreover, its availability is limited by the high cost of the equipment. For this reason, nanotechnology offers a promising approach for developing nanosystems directed at molecular targets of cardiac damage, to provide both affordable and readily available diagnostics and the possibility of targeted therapy. This review will showcase major research advances on the role of nanoparticles in cardiac fibrosis. It will discuss the advantages and limitations of nanoparticles, and the standards for advancing them to the clinical phase of treatment and diagnosis of cardiac fibrosis.Keywords: cardiac fibrosis, diagnostic imaging, therapy, nanoparticles, gold colloid